Faktor-Faktor Yang Mempengaruhi Loyalitas Anggota BMT UGT Sidogiri Capem Sempu - muhamad Annas; Nawal Ika Susanti; Siti Nur Koyimah (JPSDa: Jurnal Perbankan Syariah Darussalam, 2021)
The competitive conditions of Islamic microfinance institutions, especially in BMTs are getting tighter from time to time, so that each BMT must create a new marketing strategy in order to maintain and gain a wider share and can increase the loyalty of its members, namely by improving the company's image and the quality of Islamic services as one factor. This study aims to determine the effect of corporate image and Islamic service quality on member loyalty at BMT UGT Sidogiri either partially or simultaneously. The method used is a quantitative approach with a sample of 80 respondents who are members of the BMT UGT Sidogiri Capem Sempu. This study uses multiple linear regression analysis. The results of this study indicate that there is a significant influence between corporate image and Islamic service quality on the loyalty of members of BMT UGT Sidogiri Capem Sempu either partially or simultaneously. Variable corporate image and Islamic service quality can explain the variable loyalty of members by 89.1%, which means that the image of the company and the quality of Islamic services affect the loyalty of members at BMT UGT Sidogiri Capem Sempu by 89.1%. And the model formed is Member Loyalty = 0.591 + 0.186 Corporate Image + 0.660 Islamic service quality.